Corporate governance and Earnings management: Case of Chinese companies - Huang, Mengqian (2022)
This dissertation aims to consider conducting research into the connection between Earnings management (EM) and Corporate governance (CG), as well as the degree to which that relationship exists. This study focuses on a subset (n=301) of firms that will be trading on the Shenzhen Stock Exchange between 2016 and 2020. In order to quantify the extent to which firms that are included on the Shenzhen Stock Exchange engage in EM, this study adapts the Jones model from prior studies in the accounting field. The paper used a fixed-effects panel data model to conduct regression analysis and hypothesis testing, which used the modifiable Jones model's easily manipulated accumulated earnings as the dependent variable and the aspects of CG as the independent variables, and control variables serving as the controls. The study's findings indicate that a negative relationship exists between EM and board independence, firm size, audit committee independence, CEO duality, and board size. On the other hand, a positive relationship exists between EM and the number of board meetings.